2017
DOI: 10.1111/cas.13296
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic value of serum Epstein–Barr virus antibodies in patients with nasopharyngeal carcinoma and undetectable pretreatment Epstein–Barr virus DNA

Abstract: Epstein–Barr virus (EBV) is closely associated with nasopharyngeal carcinoma (NPC). Serum IgA antibodies against early antigen (EA‐IgA) and viral capsid antigen (VCA‐IgA) are the most commonly used to screen for NPC in endemic areas. However, the prognostic value of serum EA‐IgA and VCA‐IgA in patients with NPC is less clear. We hypothesize that serum EA‐IgA and VCA‐IgA levels have prognostic impact for survival outcomes in NPC patients with undetectable pretreatment EBV (pEBV) DNA. In this series, 334 patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
20
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 29 publications
(24 citation statements)
references
References 34 publications
2
20
0
2
Order By: Relevance
“…Dynamic monitoring of plasma EBV‐DNA can be used as a predictor for disease recurrence and treatment response in NPC patients . Detectable EBV‐DNA in plasma also provided a possibility for us to monitor treatment response in GC patients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Dynamic monitoring of plasma EBV‐DNA can be used as a predictor for disease recurrence and treatment response in NPC patients . Detectable EBV‐DNA in plasma also provided a possibility for us to monitor treatment response in GC patients.…”
Section: Discussionmentioning
confidence: 99%
“…Dynamic monitoring of plasma EBV-DNA can be used as a predictor for disease recurrence and treatment response in NPC patients. 17,36,37 Detectable EBV-DNA in plasma also provided a possibility for us to monitor treatment response in GC patients. In our study, we prospectively monitored the change in plasma EBV-DNA in Stage IV EBVaGC patients and found that EBV-DNA decreased when the patients had PR or stable disease, while it increased when the disease progressed.…”
Section: Discussionmentioning
confidence: 99%
“…Other prognostic factors include patient age and sex, molecular risk factors, lymph metastasis, and treatment regimens . Plasma EBV DNA has also been shown to be a predictive biomarker in patients with endemic NPC . However, as the results have been inconsistent, there is no consensus on the prognostic significance of the histological subtypes of NPC …”
Section: Introductionmentioning
confidence: 99%
“…10 Plasma EBV DNA has also been shown to be a predictive biomarker in patients with endemic NPC. 11,12 However, as the results have been inconsistent, there is no consensus on the prognostic significance of the histological subtypes of NPC. 13 This study aimed to examine the impact of histological subtype on survival in a large cohort of NPC patients based on the Surveillance, Epidemiology, and End Results (SEER) Program, a well-constructed database from multiple institutions in the United States.…”
Section: Introductionmentioning
confidence: 99%
“…[13]However, Yao et al did not confirm the role of VCA-IgA as a prognostic biomarker among patients with NPC and undetectable EBV DNA. [24] A possible explanation for these contradictory results may be that the previous study obtained the positive results by IFA, although Yao et al uses ELISA (Beier kit). In the absence of calibrators, inter-assay differences among ELISA kits may affect the outcome, as explained in the limitations of this article [24] and was confirmed in our study (Total CV =43.11%), confirming once more the importance of the reference in VCA-IgA ELISA detection.…”
Section: Discussionmentioning
confidence: 96%